Financial impact of ultrasound-guided lumbar plexus and sciatic nerve blocks with electrostimulation for tibial plateau leveling osteotomy surgery in dogs. (September 2019) - Warrit, Kanawee; Griffenhagen, Gregg; Goh, Clara; Boscan, Pedro
Abstract: Objective: To determine the anesthesia cost from ultrasound-guided lumbar plexus and sciatic nerve blocks confirmed with electrostimulation for unilateral tibial plateau leveling osteotomy (TPLO) surgery in dogs. Study design: Prospective, randomized, blinded clinical trial. Animals: A group of 20 dogs weighing 33.9 ± 6.0 kg (mean ± standard deviation). Methods: All dogs were administered hydromorphone and atropine, propofol for induction of anesthesia and isoflurane for maintenance. Hydromorphone and carprofen were administered for recovery. The dogs were randomly assigned to one of two groups, lumbar plexus and sciatic nerve blocks with ropivacaine [regional anesthesia (RA)] or sham blocks with saline [control (CON)]. Fentanyl was administered for rescue analgesia intraoperatively and postoperatively. The cost to manage anesthesia was divided into fixed and variable costs using the micro-costing method. The variable costs were compared using Student's t test or Mann–Whitney U test. Results: The fixed anesthesia costs were equal between groups at US$354.00 per case. The variable anesthesia cost range was US$27.90–100.10 for RA and US$21.00–180.50 for CON. Overall, cost per dog in CON was from –US$6.9 to US$80.4 compared with RA. For 160 TPLO cases per year, hospital cost when RA is performed decreased the cost by $12, 864 per year up to increased cost by $1104 per year, depending on the requirements for systemic drugs and incidence/severity of anesthesia complications. The estimated fee charge per case for service necessary to reimburse the cost of a new ultrasound (US$25, 000.00) and nerve locator (US$925.00) over their life span of 6 and 10 years, respectively, is US$26.62. Conclusions and clinical relevance: Ultrasound-guided lumbar plexus and sciatic nerve blocks with electrostimulation confirmation can increase the anesthesia cost through use of specific equipment. However, in most cases, the anesthesia cost decreased as a result of decreased costs for pain management and treatment of complications.